Manajemen Program Suka Sapi (Satu Keluarga Satu Sapi) Tahun 2021 Di Kabupaten Solok Selatan - Putri A, Oktariza; Putera, Roni Ekha; Koeswara, Hendri (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2023)
The One Family One Cow Program is one of the flagship programs of South Solok Regency which in 2021 will be realized for the first time in an effort to improve the welfare of its community. Communities who are members of farmer groups are targeted for program implementation with the South Solok Regency Agriculture Office which is the OPD supervisor, especially in the Livestock and Animal Health Sector. As a flagship program, its implementation is also expected to make South Solok Regency competitive in terms of beef production and animal protein sources in West Sumatra Province. This study aims to analyze the management of the 2021 One Family One Cow Program in South Solok Regency. This research uses qualitative methods with a descriptive type. Data collection techniques are carried out by interviews, observation and documentation. The data validity technique that researchers use is source triangulation. The selection of informants is carried out by snowball sampling technique. This research uses the theory of Management Process proposed by William H. Newman.The results of the study using the Management Process theory proposed by William H. Newman show that management in the implementation of the One Family One Cow Program in 2021 in South Solok Regency has not been carried out properly. This is marked by the findings of researchers in the field that the planning variables, namely the indicators of goal setting, are clear but the success of the program has not been achieved. In the variable of work control, there is still a lack of coordination between program implementers. On the supervisory variable also has not run well.